Analysis of spectrum of ovarian tumours: a study of 55 cases - Nishal, Arpita J.; Naik, Kinnari S.; Modi, Jigna (International Journal of Research in Medical Sciences, 2017)
Background: Malignant epithelial tumours are the most common ovarian cancers and also the most lethal gynaecological malignancies. This study was undertaken to analyse histomorphological spectrum and clinicopathological correlation of ovarian tumours. Methods: This retrospective study was done for the period of one year at Department of Pathology, New Civil Hospital, Surat, which is a tertiary health care center. Here we studied 55 cases of ovarian mass received in formalin, which were subjected to histopathological examination and immunohistochemistry as and when required. Results: In total, 55 ovarian tumour specimens were examined. Out of which 28 cases (51%) were benign, 3 cases (5%) were borderline and 24 cases (44%) were malignant. Most common histological type was surface epithelial tumours (60%) followed by germ cell tumours (13%). The commonest benign tumour was mucinous cystadenoma and commonest malignant tumour was serous adenocarcinoma. Malignancy was quite common in ovarian masses in our institute. Conclusions: Ovarian tumours are quite common in our set up and epithelial tumours are the commonest variety of ovarian tumours. The histological type of ovarian tumour correlates with the prognosis of the tumour.